Formulasi dan Evaluasi Gel Aloe vera–Andaliman (Zanthoxylum acanthopodium) untuk Penyembuhan Luka Epidermolisis Bulosa: Pendekatan Fitokimia, In Silico, dan In Vivo - Farah Dhiba; Mawandha Sari Harahap; Sony Eka Nugraha (Journal of Pharmaceutical and Sciences, 2026)
Epidermolysis Bullosa (EB) is a rare genetic skin disorder characterized by chronic wounds and delayed healing, requiring alternative therapies that support tissue regeneration. This study aimed to develop and evaluate a gel formulation containing Aloe vera extract and Andaliman (Zanthoxylum acanthopodium) essential oil for EB wound healing. The novelty of this study lies in the combination of Aloe vera and Andaliman as a topical phytopharmaceutical approach for EB-like wounds. This combination was selected based on the complementary mechanisms of Aloe vera, which supports wound healing, fibroblast activity, and re-epithelialization, and Andaliman, which exhibits antioxidant, antimicrobial, and anti-inflammatory properties. Phytochemical screening, GC–MS analysis, antioxidant assay, gel evaluation, in silico docking against VEGF-A, and in vivo testing in EB-like wound rats were performed. Phytochemical screening revealed alkaloids, flavonoids, saponins, tannins, steroids, and glycosides. GC–MS identified 38 compounds in Aloe vera and 20 compounds in Andaliman. Antioxidant testing showed IC50 values of 165.2 µg/mL for Aloe vera and 98.7 µg/mL for Andaliman. The gel formulations showed acceptable physicochemical properties, with pH 5.8–6.1, viscosity 3,800–4,700 cPs, and good adhesion. Docking results showed strong interactions of lupeol, anthranol, and paulownin with VEGF-A. In vivo, F3 (4% Aloe vera and 3% Andaliman) accelerated wound closure, improved epithelialization, reduced inflammatory infiltration, and significantly increased VEGF expression (p < 0.0001). These findings suggest that Aloe vera–Andaliman gel is a promising topical candidate for EB wound management.